2008
DOI: 10.1111/j.1567-1364.2008.00420.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a carbon source on polyphosphate accumulation inSaccharomyces cerevisiae

Abstract: The cells of Saccharomyces cerevisiae accumulate inorganic polyphosphate (polyP) when reinoculated on a phosphate-containing medium after phosphorus starvation. Total polyP accumulation was similar at cultivation on both glucose and ethanol. Five separate fractions of polyP: acid-soluble fraction polyP1, salt-soluble fraction polyP2, weakly alkali-soluble fraction polyP3, alkali-soluble fraction polyP4, and polyP5, have been obtained from the cells grown on glucose and ethanol under phosphate overplus. The dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…Reported evidence indicated that different extraction methods may result in size fractionation of recovered polyP 29. To test possible purification method-dependent differences in the length and recovery of polyP, we extracted polyP from two aliquots of yeast cultures by the phenol/chloroform (pH 8.0) method and samples were purified either by ethanol precipitation or by column chromatography (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…Reported evidence indicated that different extraction methods may result in size fractionation of recovered polyP 29. To test possible purification method-dependent differences in the length and recovery of polyP, we extracted polyP from two aliquots of yeast cultures by the phenol/chloroform (pH 8.0) method and samples were purified either by ethanol precipitation or by column chromatography (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…In the parent strain, with ethanol used as a carbon source, the content of acid-soluble fractions was lesser than that on glucose, while the content of PolyP3 and PolyP5 was higher. Such effect was observed earlier in the wild type strain [9]. The results of electrophoresis of PolyP accumulated during 30 min in the (+P) medium with glucose are shown in Figure 3.…”
Section: Resultsmentioning
confidence: 84%
“…PolyP plays the key role in the processes of biomineralization and phosphorus homeostasis [6,7]. The cells of Saccharomyces cerevisiae under certain growth conditions are able to accumulate PolyP in great amounts strongly depending on the growth stage, culture conditions, and a carbon source [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…-In view of the great role of PolyP in cell metabolism, bone tissue development, and blood coagulation, it is necessary to control its amounts in food. Enzymatic methods using polyphosphate kinase and exopolyphosphatases are of interest for PolyP detection in biological samples (Ault-Riché et al 1998;Vagabov et al 2008). -The importance of polyphosphate kinases ppk1 and ppk2 in bacterial metabolism and virulence of pathogens is of interest for the development of new inhibitors that may be prospective antibacterial compounds.…”
Section: Resultsmentioning
confidence: 99%